H-2-restricted cytotoxic effectors generated in vitro by the addition of trinitrophenyl-conjugated soluble proteins - Schmitt-Verhulst, A (The Rockefeller University Press, 1978)
Murine spleen cells from normal donors were cultured in vitro with trinitrobenzene sulfonate (TNBS)-conjugated soluble proteins, i.e., bovine gamma globulin (TNP-BGG) or bovine serum albumin (TNP-BSA). Addition of 100 μg of any of these TNP-proteins to the spleen cell cultures led to the generation of cytotoxic T-cell effectors which were H-2-restricted and TNP- specific. The lytic potential of such effectors was comparable to that generated by sensitization with TNBS-modified syngeneic cells, and was restricted to haplotypes shared at the K or K plus I-A, or the D regions of the H-2 complex. Greater effecter cell activity was generated by addition of TNP-BGG against TNBS-modified targets which shared K plus I-A than against modified targets which shared the D region with the responding cells, which suggests that the same immune response genes are involved when the response is generated by the addition of TNP-conjugated soluble proteins or of TNBS- modified cells. H-2-restricted, TNP-specific effecter cells were generated by culturing mouse spleen cells with syngeneic cells which had been preincubated with TNP- BGG or TNP-BSA for 1.5 h. The addition of unconjugated soluble proteins to the cultures did not result in cytotoxic effectors detectable on H-2-matched targets, whether the targets were prepared by modification with TNBS, or by incubation with either the unconjugated or TNP-conjugated proteins. Depletion of phagocytic cells in the tumor preparation by Sephadex G-10 column fractionation before incubation with TNP-BSA had no effect on their lysis by the relevant effector cells. Immunofluorescent staining of tumor target cells with anti-TNP antibodies indicated that TNP could be detected on the tumor cells within 10 rain of incubation with TNP-BSA. The cytotoxic response generated by addition of the TNP-proteins to spleen cell cultures was found to be T-cell dependent at the effector phase, as shown by the sensitivity of the lytic phase to absorbed RAMB and complement. Furthermore, the response did not appear to be attributable to antibody-dependent cellular cytotoxicity. Three mechanisms were considered which could account for the generation of H-2-restricted, TNP-specific, cytotoxic T-cell effectors by the addition of soluble TNP-proteins. These include covalent linkage of activated TNP groups from the soluble proteins to cell surface components, macrophage processing of the soluble conjugates and presentation to the responding lymphocytes in association with H-2-coded self structures, or hydrophobic interaction of the TNP-proteins to cell surfaces. Results obtained from sodium dodecyl sulfate gel patterns indicating that cell-bound TNP was still linked to BSA, and the observation that phagocytic-depleted cells could interact with the soluble TNP-proteins and function as H-2-restricted targets, appear not to favor the first two proposed mechanisms.